KREATIVITAS GURU PAI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK DI SMP NEGERI 1 MERBAU MATARAM - Mahyuddin (UNISAN JURNAL, 2024)
Islamic Religious Education (PAI) teachers must also be creative because it is important that the teaching and learning process can run well and not be boring. Teacher creativity is also important in achieving student learning outcomes. This research aims to determine teacher creativity in an effort to increase student motivation when learning. This type of research is field research using a qualitative descriptive approach. In data collection, data collection techniques were used in the form of purposive sampling, snowball sampling. The method used in data collection is the observation method as the main method, the interview method and the documentation method as the supporting method. Meanwhile, qualitative analysis was used for data analysis with stages of data reduction, data presentation and drawing conclusions. Conclusions are drawn by inductive thinking. From the research results, the author can conclude that teacher creativity in increasing student learning motivation is effective in increasing student motivation, this is proven by the increase in student learning outcomes at the end of the semester by obtaining grades above the average. Other evidence can be seen from the students’ activeness in participating in the teaching and learning process even though the school facilities are inadequate.